How to improve Job Satisfaction and Organizational Citizenship Behavior through Transformational Leadership and Organizational Culture? (Study on Employees of PT Anugrah Agung Pratama Kota Kediri) - Danastya Fahreza; Langgeng Setyono; Gunawan Nurtjahjono (Equity: Jurnal Ekonomi, 2023)
The corporation must increase employee voluntary attitudes, organizational citizenship behavior, and job happiness in order to enhance employees' potential job performance. This study is important for determining the effect of transformational leadership and organizational culture on work satisfaction and the promotion of organizational citizenship behavior. This study employs a quantitative methodology to collect data from 32 employees utilizing a saturation sampling technique. With the assistance of SmartPLS software, the data were analyzed using the PLS-based SEM approach. The results indicated that transformational leadership has no influence on job satisfaction, organizational culture has a significant positive influence on job satisfaction, transformational leadership has no influence on organizational citizenship behavior (OCB), organizational culture has an influence on OCB, job satisfaction does not mediate the influence of transformational leadership on OCB, but it does mediate the influence of organizational culture on OCB. These findings aid PT Anugrah Agung Pratama in increasing job satisfaction and employee OCB.